Strategi Branding UMKM “Pentol Jan Larrise” Melalui E-Commerce Di Era Digitalisasi - R, Natasya Eka; Pudjoprastyono, Hery (Journal Of Human And Education (JAHE), 2024)
This activity aims to assist Micro, Small and Medium Enterprises (MSMEs) "Pentol Jan Larrise" in improving their branding and marketing of products in the era of digitalization. In this context, branding is very important because it can attract the attention of consumers and differentiate products from other competitors. Through this activity, UPN "Veteran" East Java Village Development Students provide assistance to MSME owners named Mr. Slamet to create a stronger product identity by creating logos, banners, and accounts on e-commerce platforms such as Shopee. With this branding strategy, it is hoped that the business "Pentol Jan Larrise" can spread widely in the digital era and can follow market trends where competition is increasingly fierce nowadays.